Report on the analysis of questionnaire responses from the survey of Decision Makers...to determine the Information Seeking Habits of these Officials (CCCRIS/CARICOM Project [Georgetown]GY, 1995)
Reports on a user study to determine the information needs and information seeking habits of a key group of managers in the region.
DC